The role of China for trade Liberalization and competition policy after WTO accession; National Security vs. Anti-Dumping agreement, What ailing the WTO? - Wang, Yuhui; Mushtaq, Shahzada Aamir (The journal of contemporary issues in business and government, 2021)
The operation of World Trade Organization (WTO) remained suspended and revived several times over the past few decades. The mandate was given to World Trade Organization (WTO) to ensure economic efficiency in international trade while allowing for the optimal use of world’s resources in line with the objective of sustainable development, to establish reciprocal and mutually advantageous arrangements in order to substantially re-duce the unjustified tariff’s and other trade frictions and abolishment of discriminatory conduct in global trade by accelerating the multilateral trading systems. For seven decades the safeguard measures in Multilateral Trading Phase (MTP) remain stagnant before being incorporated in 1994. However, alleged security instances already prevail in many other (WTO) provisions, including the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and Agreement on safeguards. The excessive application of article XXI (a)(i) of GATT posing explosive trade disputes including Violative tariff’s fixed by the United States and like trade limitations inflicted by Russia and the United Arab Emirates (UAE)challenged the statutory framework and existence of the World Trade Organization. It has raised a question that how these “parturient trade constraints” under the umbrella of security exceptions be interpreted or imposed? Either these are self-judging, binding through judicial precedent, or institutional interpretation? The members of WTO shall take this as a matter of grave concern in order to rejuvenate the escalating challenges to international trade and to reinstate the equitable competitive business atmosphere for all entrants globally. The WTO being symbolic international trade institution shall have to make speaking ruling on the scope, meaning and application of these security exceptions. The protectionist tariffs recommended by the International Trade Commission (ITC) and Commerce Department of United States are not in line with the spirit of GATT, Anti-Dumping Agreement and Agreement on Safeguards. The World Trade Organization (WTO) will have to take serious initiatives for international regulation of Anti- Dumping Measures.